How stem cell therapy can act in the treatment of patients with Covid-19 - Rainho, Mateus A.; de Azevedo, Aline A.; Paris, Gustavo C.; Ferreira, Adriana L.; Azevedo, Yanca M. de A.; Sodré, Júlia L. T.; Mynssen, Giovana S. de L.; de Oliveira, Genilza P.; Silva, Karina R.; Cortez, Erika A. C.; Stumbo, Ana C.; Carvalho, Simone N.; et al. (Brazilian Journal of Health and Biomedical Sciences, 2022)
Introduction: The emergence of a new coronavirus has changed the world and caused one of the biggest global health crises of the past 100 years. The protagonist of the pandemic, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is responsible for the coronavirus disease 2019 (Covid-19), which leads to dysfunctions in a plethora of systems, especially in severe cases. Therefore, researchers and healthcare professionals are making great efforts to develop a therapy that helps the many organs affected by the disease, for which mesenchymal stem cells (MSCs) arise as promising candidates. MSCs can offer benefits at different phases of Covid-19, since they have important anti-inflammatory and tissue repair properties. Objective: This review aims to elucidate how MSCs can contribute in the Covid-19 scenario by considering their properties and mechanisms of action. Methods: A review of the scientific literature was conducted on electronic databases, such as PubMed, Scielo and Web of Science, in the period of 2020-2021. Results: Therapeutic effects of MSCs in preclinical models of respiratory, nervous, renal, and cardiovascular systems were observed. Conclusion: MSCs can be a therapeutic resource for patients with severe Covid-19. Keywords: SARS-CoV-2; Covid-19; Mesenchymal stem cells; Immunomodulation; Cell therapy.